Port cybersecurity : securing critical information infrastructures and supply chains - Polemi, Nineta (Elsevier, 2018)
Port Cybersecurity: Securing Critical Information Infrastructures and Supply Chains examines a paradigm shift in the way ports assess cyber risks and vulnerabilities, as well as relevant risk management methodologies, by focusing on initiatives and efforts that attempt to deal with the risks and vulnerabilities of port Critical Information Infrastructures (CII) ecosystems. Modern commercial shipping ports are highly dependent on the operation of complex, dynamic ICT systems and ICT-based maritime supply chains, making these central points in the maritime supply chain vulnerable to cybersecurity threats. Identifies barriers and gaps in existing port and supply chain security standards, policies, legislation and regulatory frameworksIdentifies port threat scenarios and analyzes cascading effects in their supply chainsAnalyzes risk assessment methodologies and tools, identifying their open problems when applied to a port's CIIs.